Peran Satuan Lalu Lintas Polres Kuningan Dalam Mengurai Kemacetan Melalui Rekayasa Lalu Lintas - Rudolf Kasenda (Indonesian Journal of Police Studies, 2021)
Kuningan Regency is geographically a plateau area with cool weather and is dominated by natural attractions which are an attraction for this Regency. Because it makes a lot of local and foreign tourists visiting the Kuningan district for a vacation and enjoy its natural beauty. Every year traffic jam is always an annual phenomenon especially during the Eid holidays, Christmas and New Year. The Kuningan police traffic unit has the role of creating security, safety and order for road users, especially in congestion which always happens every year in Kuningan District. This study aims to analyze and describe the role and factors that influence the implementation of traffic jams by the Kuningan police traffic unit. Research locations in Kuningan Police with a focus on Decomposition of Congestion. Using data triangulation (Moleong; 2006: 330) 4 (four) kinds of techniques namely sources, theories and techniques as well as primary, secondary data sources. Data validity is data reduction, data display, conclusion drawing and verification. This research uses POAC theory and Role theory and uses the concept of Traffic Engineering Management. The implementation of traffic engineering is less than the maximum performed by the Brass Traffic Police Unit analyzed from the planning function. Forming a strategy for breaking down traffic, organizing, namely the preparation of member plots placed at various points that are sources of vulnerability, implementation and control, namely assessment and monitoring in past engineering activities. traffic carried out by the Kuningan Police Traffic Unit. In the implementation of traffic engineering there are internal factors that influence are the factors of people, budget, facilities and infrastructure to support the breakdown of congestion. Then the external factors that influence are road factors which become the location of vulnerability. The conclusion that becomes an obstacle to engineering by the Kuningan police traffic unit is the competence of members, budget, strategy, facilities and supporting infrastructure in implementing traffic engineering.